THE SEDIMENTATION RATE OF THE BIOLOGICAL ACTIVITIES OF INFLUENZA A VIRUS - Lauffer, Max A. (The Rockefeller University Press, 1944)
The sedimentation rates of the mouse infectivity principles of the PR8 and the F12 strains of influenza A virus were shown by studies in the separation cell to have values which are not significantly different from sedimentation rates of the principal components of purified preparations. It was shown further that the bulk of the chicken red blood cell agglutinating activity and of the chick embryo infectivity of PR8 influenza virus preparations sediments at the same rate as that of the 100 mµ. component. Some activity was shown to be associated with aggregates. These results lend strong support to the assumption that the three biological activities are associated with the particles characterized as spheres with a diameter of about 100 mµ.